The NaBH4 Reduction and pH Effects on the Optical Property of Bismuth Vanadate - Riapanitra Anung; Julian Haryanto Michael; Setyaningtyas Tien; Riyani Kapti; Nur Handayani Santi (E3S Web of Conferences)
In this study, oxygen vacancies were created on the surface of BiVO4 nanoparticles using the NaBH4 reduction technique, resulting in BiVO4−x samples that are oxygen-deficient. Optical absorption data using a UV-visible diffuse reflectance spectrophotometer showed that the reduction process increases the maximum absorption edge to 575 nm and reduces the band gap energy to 2.78 eV at high pH. Furthermore, modulating pH during synthesis allowed tuning of the electronic structure and surface states of BiVO₄, which significantly impacts the photocatalytic efficiency. Higher pH levels during reduction led to narrower band gaps and enhanced visible-light responsiveness. These vacancies should serve as charge traps and adsorption sites, improving the charge transport within the BiVO₄ matrix by limiting electron-hole recombination. This improves photogenerated electron availability, enabling better pollutant photodegradation and water oxidation potential in environmental applications. The study highlights the role of NaBH₄ as a reduction, effectively creating oxygen vacancies and optimizing photocatalytic performance. This research underscores the potential of engineered BiVO₄ nanoparticles with tailored oxygen vacancies for advanced photocatalytic applications, especially in environmental remediation.